INTERNALISASI AJARAN PANCA DHARMA TAMANSISWA, KEMAMPUAN SELF-REGULATED LEARNING, DAN PRESTASI AKADEMIK MAHASISWA - Andreas Yudha Fery Nugroho (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2020)
This study focuses on two factors that might correlate with the academic achievement of Sar-janawiyata Tamansiswa (UST) students. These two factors are the internalization of the teachings of the five Dharma Tamansiswa and the ability of self-regulated learning. Academic achievement is a benchmark of student success in each semester or at the end of the lecture period (graduation). Academic achievement is a result that can be fought for by all students in accordance with the tar-gets to be achieved respectively. The purpose of this study is to reveal whether the internalization of the teachings of the five Taman dharma Tamanasiswa and self-regulated leaning abilities corre-late with student academic achievement. The research process starts from curiosity and concern for UST students' academic achievement. Academic achievement is the result of evaluating whether the student is successful or not in each semester. This research is a Quantitative Regression Corre-lation research using a survey method for distributing attitudes and or behavioral scales. The scale is a psychological measurement tool to assess individuals in attitude and action. The scale is a de-scription of students on the variable internalization of the teaching of the five dharma and the abil-ity of self-regulated learning. While academic achievement can be seen from the results of student GPA.Keywords: Internalization of the teaching of the five dharma tamansiswa, self-regulated learning and Student Academic Achievement.